Education for Sustainable Development in Science Classrooms: A Bibliometric Analysis and Literature Review - Nuwangi, Pohaci Puspa; Riandi, Riandi; Widodo, Ari (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2024)
Education for sustainable development is an intriguing and evolving topic. There is a potential to integrate sustainable education with science education as both share aligned goals and can mutually support each other. Therefore, this article aims to visualize research trends on sustainable education in science classrooms over five years (2019-2023) to explore new potential research innovations in the related field and identify strategies that can be applied to integrate sustainable values into science education. Data were obtained from one of the most significant publication sources, Scopus, resulting in 134 research articles. The data were processed using two methods, namely bibliometric analysis and systematic literature review, assisted by VOSviewer software and Microsoft Excel 2016. The analysis indicates a consistent upward trend in research on this topic, reaching 45 publications in 2022 and declining to 36 in 2023. Additionally, seven clusters were identified from the visualization map, each containing 2-8 keywords. On the other hand, the analysis in the systematic literature review reports that there are five strategies to incorporate sustainable education into science classrooms.